Pengaruh Ulasan Pelanggan Daring dan Berbagi Pengetahuan Konsumen pada Keputusan Pembelian di TikTok Shop - Febiani, Tyas; Sari, Kartika; Slamet , Slamet (Brainy: Jurnal Riset Mahasiswa, 2023)
Society prefers to utilize the media in the process of selecting the products they will buy, this will affect the different impressions and perceptions of consumers between purchasing offline and buying products online. The purpose of this study is to examine the impact of online customer reviews and consumer knowledge sharing on purchasing decisions at the TikTok Shop. The population in this study are TikTok Shop users who are domiciled in Central Java. In this study, a questionnaire was employed as a data collecting tool. The number of samples in this study were 200 respondents. The research's analytical method is multiple linear regression analysis and processed using SPSS version 25. The results of the study partially show that online customer reviews have a positive influence on purchasing decisions at TikTokShop, and sharing consumer knowledge also has a positive influence on purchasing decisions at TikTokShop. Simultaneously the results show that online customer reviews and consumer knowledge sharing have a positive influence on purchasing decisions on TikTokShop.